Expectations Towards Vocational Training for Employment in Spain and its Impact on the Labour Market - Vidigal-Alfaya, Susana; Ballesteros-Moscosio, Miguel-Ángel (Journal of Technical Education and Training, 2024)
The necessity to adapt to the volatility of the labour market, coupled with the imperative to enhance the competencies associated with our professional roles, renders continuous training a fundamental requirement. In an era characterised by rapid technological advancements and shifting market demands, ongoing professional development is essential not only for individual adaptability but also for the overall efficacy and productivity of organisations. Cultivating a culture of lifelong learning is therefore critical in navigating the complexities of the contemporary work environment. This study aims to explore the expectations of both employed and unemployed individuals in Spain regarding this training system, as well as the tangible impact that training has had post-participation. A quantitative study was conducted using a questionnaire analysed through descriptive, correlational, and inferential statistics. The results, derived from responses by 390 (49% employed,51% unemployed) trainings users, reveal high expectations among both employed and unemployed individuals concerning vocational training for employment. Moreover, the training positively influences the self-esteem of unemployed participants. However, this group does not report a significant impact on the relationship between training and their integration into the job market. In contrast, employed individuals experience a more pronounced impact regarding workplace improvements following the completion of training. These findings underscore the necessity of raising awareness about this training system and its implications, as well as the preparedness it imparts to its users. Efforts to enhance visibility will be essential for facilitating a quicker and more effective reintegration of unemployed individuals into the labour market.